JATIMPRO: A Native Species Reinforcement through the Penta Helix Approach in Brantas Watershed Management - Nurina Fitriani; Muhammad Fakhri; Arie Wardhono; Otto Fajarianto; Edi Jadmiko; M. Bagas Pramudya Pratama; Zevania Zullianne Kurniawan (Universitas Diponegoro, 2026)
The Brantas Watershed is a critical hydrological zone in East Java, underpinning essential services such as raw water supply, irrigation, industrial operations, and the livelihood of surrounding communities. However, shifts in land utilization, deforestation, and escalating pollutant inputs have significantly impaired water flow regulation, degraded the integrity of the watershed, and compromised water quality particularly in upstream regions that are crucial for water provisioning. These challenges present substantial threats to the long-term viability of regional water resource management. In response, a collaborative initiative led by a consortium of East Java’s public universities aims to promote sustainable watershed governance. The program emphasizes the restoration of spring ecosystems, the reinforcement of native plant species, and the mobilization of local communities. Reforestation with indigenous vegetation has demonstrated positive impacts on both ecological resilience and watershed hydrology. Moreover, the adoption of inclusive governance models such as the pentahelix approach has fostered cross sector collaboration, ensuring shared responsibility and adaptive management. Integrating ecological restoration with multi actor institutional frameworks is vital to safeguarding water security and preserving the Brantas Watershed ecological function.